Evaluación de la calidad de agua en sistemas acuapónicos para la producción de chame (Dormitator latifrons) en el área Agropecuaria, ESPAM-MFL - Mera Vélez, Alondra Gardenia (2025)
This study assessed water quality in aquaponic systems designed for the production of Chame (Dormitator latifrons) in the agricultural area of ESPAM-MFL, with the objective of determining the feasibility of these systems in terms of water quality and their impact on the growth of fish and vegetables, three treatments with different fish densities were implemented, evaluating physicochemical and biological water parameters such as ammonium, pH, dissolved oxygen, and electrical conductivity. The results indicated that the treatment with the lowest fish density (T1) exhibited the best performance and water quality, with average ammonium levels of 0.5 mg/L, dissolved oxygen at 5.2 mg/L, and a final quality score of 84.26/100. In contrast, the treatment with the highest fish density (T3) recorded ammonium peaks exceeding 2 mg/L and lower dissolved oxygen levels at 3.63 mg/L, these variations were partially mitigated through improvements in aeration and energy automation, however, it should be noted that the null hypothesis (H0) was accepted, as T1, T2, and T3 exhibited similar behavior, supported by statistical analysis, which found no significant differences among the evaluated parameters. To ensure proper monitoring, a strategic guide was developed for the sustainable and efficient production of Chame, emphasizing the importance of proper aquaponic system design and efficient water resource management, these findings highlight the need for future research on long-term sustainability and the impact of extreme climatic events on aquaponic systems.